Youth engagement in #AASW6 is important for ownership of outcomes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Courtney Paisley, YPARD Coordinator, talks about having youth engagement at #AASW6 The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/